The structure , magnetism and EPR spectra of a (μ-thiophenolato)(μ-pyrazolato-N,N') double bridged dicopper(II) complex - Khadir, Narjes (2014)
A new binuclear copper(II) complex, namely [Cu2L(pz)(DMSO)], where L = 2,6-bis[(2-phenoxy)iminomethyl]-4-methylthiophenolate(3-) and pz = pyrazolate ligand, has been synthesized by a one-pot synthesis involving copper(II) acetate monohydrate, the S-protected ligand precursor 2-(N,Ndimethylthiocarbamato)-5-methylisophthalaldehyde di-2?-hydroxy anil, (I), and pyrazole, in which a metal-promoted S-deprotection reaction occurs during the formation of the complex. This was characterized by routine physicochemical studies, single crystal X-ray diffraction and electron paramagnetic resonance (EPR) techniques. The structure analysis reveals that there are copper centres in two different environments, a slightly distorted square planar and a distorted square-pyramidal, arranged in binuclear units. The EPR study of these binuclear units performed at 9.4 GHz in the temperature range between 4 and 293 K shows an antiferromagnetic interaction between CuII ions, and allows evaluating g factors gx = 2.068(1), gy = 2.091(1) and gz = 2.165(1), with <g> = 2.108(1), an exchange coupling parameter J0 = -26(1) cm−1 (defined as Hex = - J0 S1 S2), and a zero field splitting of the ground triplet state described by D = 86(2) × 10-4 cm-1 and E = -48(3) × 10-4 cm-1. These results are discussed and compared with the existing literature.